University Education for Business : a Study of Existing Needs and Practices - Bossard, James H. S. (University of Pennsylvania Press, 2017)
An exhaustive survey of the subject, from both the economic and academic points of view, with pertinent suggestions for a closer harmony between collegiate training and the modern business world.